Self-efficacy for learning beliefs in collaborative contexts: relations to pre-service early childhood teachers’ vicarious teaching self-efficacy - Yim, Eunice Pui-yu (Frontiers in Education, 2023)
The importance of academic self-efficacy generally outweighs social self-efficacy in teacher training in academia. Given the teaching profession is collaborative career, social self-efficacy should play a significant role in the success of teacher training within and outside of academia. Students taking an early childhood teacher training program in a tertiary institute in Hong Kong (N = 513) responded to survey items concerning three personal self-efficacy for learning variables (academic self-efficacy, social self-efficacy and control of learning) and vicarious experiences as a source of teaching self-efficacy. Academic self-efficacy, social self-efficacy and control of learning were found to be (1) related but distinctive to one another, and (2) positively related to vicarious experiences as a source of teaching self-efficacy. Practicum experience was found to have no significant impact on any of the personal self-efficacy for learning variables and the social-oriented vicarious source of teaching self-efficacy. This study suggested that as a source of teaching self-efficacy for pre-service teachers, vicarious experiences could be as important as experiences of teaching skills mastery. Moreover, practicum that does not optimize the interplay of personal self-efficacy for learning variables with vicarious experiences as a source of teaching self-efficacy, and does not fully consider cultural sensitivities, would not contribute significantly to teachers’ learning and social competence. The development of different domains of self-efficacy is not only affected by different sources of teaching self-efficacy but also varies between pre-service and experienced teachers. This study renewed the existing understanding of the reciprocal influences of personal self-efficacy for learning and vicarious experiences as a source of teaching efficacy, which can be fostered by teacher education programs. Future studies will be required to explore the culturalization of sources of teaching self-efficacy, how different components of personal self-efficacy for learning change over career stages and time, and how the transfer of learning between practicum and academia can be further enhanced.